El futuro se repite: priming effects in Spanish future expressions - Lamberti, Luana; Salgado, Hugo (Revista da ABRALIN, 2021)
Spanish shows variation between two future expressions. The synthetic future (SF) is marked morphologically while the periphrastic future (PF) is constructed with the verb ir ‘to go’ and an infinitive. Previous studies have described the semantic factors that determine the use of these expressions. The effects of priming in the selection of these expressions have yet to be addressed. Our results showed that a combination of factors contributes to the occurrence of the SF: priming effect; certainty; and verb frequency. We demonstrated that cognitive factors in combination with semantic ones should be taken into consideration when talking about the variation between the SF and the PF in Spanish. Our study also provides evidence for the fact that the obsolescing construction, the SF, will have a stronger priming effect in the larger process of language variation and change. Our work offers an important addition to the literature about the effects of persistence and entrenchment in language since we demonstrated that speakers are sensitive to contextual activation and language use factors.